Evaluating the Spike–hACE2 interactions in the wild type and variants of concern of SARS -CoV-2 at different temperatures - Mandal, Nabanita; Rath, Soumya Lipsa (Frontiers in Physics, 2024)
The effect of temperature on SARS-CoV-2 is frequently debated upon. There is evidence of temperature sensitivity of the viral proteins; however, how heat influences the protein-protein interaction between a SARS-CoV-2 protein and the human Angiotensin Converting Enzyme 2 (ACE2) receptor remains to be elucidated. Here, we studied the Receptor Binding Domain (RBD) of the surface glycoprotein of SARS-CoV-2 wild-type and variants of concern, bound to human ACE2 receptor at different temperatures, through atomistic simulations. We found that although there were no major conformation changes in the protein complexes at high temperatures, the dynamics of the proteins significantly increased. There was loss of proteinprotein contacts as well as interaction energies. Thus, the protein-protein interaction was found to be rather strong. This study would be useful for viral protein studies as well as design of peptide-based vaccines and therapeutics.